Bone morphogenetic protein-9 induces epithelial to mesenchymal transition in hepatocellular carcinoma cells - Li, Qi; Gu, Xing; Weng, Honglei; Ghafoory, Shahrouz; Liu, Yan; Feng, Teng; Dzieran, Johanna; Li, Li; Ilkavets, Iryna; Kruithof- de Julio, Marianna; Munker, Stefan; Marx, Alexander; et al. (Cancer science, 2013)
Epithelial-mesenchymal transition (EMT) is an important mechanism to initiate cancer invasion and metastasis. Bone morphogenetic protein (BMP)-9 is a member of the transforming growth factor (TGF)-β superfamily. It has been suggested to play a role in cancer development in some non-hepatic tumors. In the present study, two hepatocellular carcinoma (HCC) lines, HLE and HepG2, were treated with BMP-9 in vitro, and phenotypic changes and cell motility were analyzed. In situ hybridization (ISH) and immunohistochemical analyses were performed with human HCC tissue samples in order to assess expression levels of BMP-9. In vivo, BMP-9 protein and mRNA were expressed in all the tested patients to diverse degrees. At the protein level, mildly positive (1 + ) BMP-9 staining could be observed in 25/41 (61%), and moderately to strongly positive (2 + ) in 16/41 (39%) of the patients. In 27/41 (65%) patients, the BMP-9 protein expression level was consistent with the mRNA expression level as measured by ISH. In those patients with 2 + protein level, nuclear pSmad1 expression in cancer cells was also significantly increased. Expression of BMP-9 was positively related to nuclear Snail expression and reversely correlated to cell surface E-cadherin expression, although this did not reach statistical significance. Expression levels of BMP-9 were significantly associated with the T stages of the investigated tumors and high levels of BMP-9 were detected by immunofluorescence especially at the tumor borders in samples from an HCC mouse model. In vitro, BMP-9 treatment caused a reduction of E-cadherin and ZO-1 and an induction of Vimentin and Snail expression. Furthermore, cell migration was enhanced by BMP-9 in both HCC cell lines. These results imply that EMT induced by BMP-9 is related to invasiveness of HCC.